Factor influencing the selection of extension of time and delay analysis in legal cases [electronic resource] - Ronnie Aslina Goring, 1983- (2010)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2010